Labor productivity and remuneration across Mexico’s manufacturing industry: A spatial approach - López Cabrera, Jesús Antonio; González Mata, Enrique; Cabral Torres, René (Estudios Económicos de El Colegio de México, 2024)
This document investigates the relationship between wages and labor productivity in Mexico, considering the territorial dimension and, within it, the impact that the productivity of neighboring entities has on local wages, given the geographical proximity. Results show that an increase in labor productivity impacts remuneration. Moreover, an increase in productivity in a particular state positively impacts the remunerations of neighboring states. The results allow us to understand that territorial productivity has a spillover effect on the remunerations of neighboring territories.